HPV self-sampling implementation strategies to engage under screened communities in cervical cancer screening: a scoping review to inform screening programs - Fullerton, Madison M.; Ford, Caitlin; D’Silva, Chelsea; Chiang, Bonnie; Onobrakpor, Se-Inyenede; Dievert, Holly; Yang, Huiming; Cabaj, Jason; Ivers, Noah; Davidson, Sandra; Hu, Jia (Frontiers in Public Health, 2024)
Introduction Human papillomavirus (HPV) testing as a method of cervical cancer screening can be performed by healthcare providers or by patients through self-sampling directly in the community, removing several barriers experienced by under screened populations. The objective of this scoping review was to determine which HPV self-sampling implementation and engagement strategies have been used to engage under screened populations (i.e., Indigenous, newcomer, and rural and remote communities) in cervical cancer screening. Methods A scoping review was conducted searching MEDLINE, CINAHL, EMBASE, Cochrane Library, and SocINDEX from inception to August 2023. The inclusion criteria were: (1) Indigenous, newcomer, and rural and remote communities; (2) countries identified as members of the Organization for Economic Co-operation and Development; and (3) intervention included HPV self-sampling. The review was registered prior to conducting the search (https://osf.io/zfvp9). Results A total of 26 studies out of 2,741 studies met the inclusion criteria. In-person engagement with trusted community leaders was the most widely used and accepted recruitment and engagement strategy across all three populations. Six out of seven studies with Indigenous communities distributed HPV self-sampling kits to eligible participants in person in a clinical setting for collection on site or at home. Similarly, nine of the identified studies that engaged newcomers recruited participants in person through the community, where eligible participants were either given a kit (n = 7) or received one in the mail (n = 2). Lastly, of the 10 identified studies engaging rural and remote participants in HPV self-sampling, six recruited eligible participants in person at various community locations and four used electronic medical records or registries to identify and mail kits to participants. Discussion HPV self-sampling through in person kit distribution and mail out of HPV self-sampling kits is an effective way to increase participation rates amongst under screened populations.